Impact of Paraquat Dichloride Herbicide Application on The Dominance Dynamics and Weed Composition in Rubber Plantations (Hevea brasiliensis Muell. Arg.) - Rahmadi, Rizky; Rochman, Fajar; Priyadi, Priyadi; Effendy, Arga Satria; Cahya, Sevagus Waskita (Biofarm : Jurnal Ilmiah Pertanian, 2024)
The presence of weeds can result in a reduction in the productivity of rubber plants, necessitating the implementation of control measures. Among the various control methods, the use of herbicides derived from paraquat dichloride has been identified as a more effective and efficient approach in terms of cost and time. However, the application of weed control measures can lead to alterations in the structure and composition of weeds. The objective of this study was to ascertain the prevalence of weeds and the impact of paraquat dichloride herbicide on the composition of weeds in rubber plantations. This study employed a randomized group design with six treatments and four replications. The treatments consisted of doses of paraquat dichloride, including 310.5 g/ha (P1), 414 g/ha (P2), 496.8 g/ha (P3), 621 g/ha (P4), mechanical control (P5), and control (P6). The results demonstrated that paraquat dichloride herbicide was efficacious in the control of weeds with a rapid onset, yet exhibited a limited duration in comparison to crop-translocated herbicides. This was evidenced by the diversity of weed species dominance at SDR 4 WAA < 8 WAA < 12 WAA. The application of paraquat dichloride herbicide and mechanical control were found to induce alterations in weed composition.